К проблеме прародины носителей родственных диалектов и методам ее установления - Гамкрелидзе, T. B.
Gamkrelidze, T. V. - Ivanov, V. V., The Problem of the Original Homeland of the Speakers of Related Dialects and on the Methods of its Determination; engl. Résumé; zu I. M. Diakonoff, VDI 3/4, 1982.